Research on Geometry Teaching of High School Based on the Software of GeoGebra - Xu, Linlin; Yang, Zezhong; Liu, Yansheng (American Journal of Education and Learning, 2019)
In recent years, GeoGebra software has been widely used in high school mathematics teaching, especially in assisting high school mathematics geometry teaching. The software of GeoGebra is complex in function, teachers should use it reasonably according to its characteristics. According to the mathematics curriculum standards and the mathematics teaching theory of the Fan Hiele couple, the author thinks that the use of GeoGebra software in high school geometry teaching should follow the principles of heuristic, interactivity, flexibility and selectivity. In order to improve the efficiency of high school mathematics geometry teaching, in the actual teaching process, teachers should pay attention to setting reasonable geometric questions according to the students' geometric thinking level, minimizing unnecessary operations, combining multiple views to realize the combination of numbers and forms, and handling the relationship between students' software learning and mathematics knowledge learning, organizing and managing the classroom effectively, coordinating the relationship between the software, blackboard and courseware.